Quantum Properties of Dichroic Silicon Vacancies in Silicon Carbide - Nagy, Roland; Widmann, Matthias; Niethammer, Matthias; Dasari, Durga B. R.; Gerhardt, Ilja; Soykal, Oney O.; Radulaski, Marina; Ohshima, Takeshi; Vuckovic, Jelena; Nguyen Tien Son; Ivanov, Ivan G.; Economou, Sophia E.; et al. (AMER PHYSICAL SOC, 2018)
Although various defect centers have displayed promise as either quantum sensors, single photon emitters, or light-matter interfaces, the search for an ideal defect with multifunctional ability remains open. In this spirit, we study the dichroic silicon vacancies in silicon carbide that feature two well-distinguishable zero-phonon lines and analyze the quantum properties in their optical emission and spin control. We demonstrate that this center combines 40% optical emission into the zero-phonon lines showing the contrasting difference in optical properties with varying temperature and polarization, and a 100% increase in the fluorescence intensity upon the spin resonance, and long spin coherence time of their spin-3/2 ground states up to 0.6 ms. These results single out this defect center as a promising system for spin-based quantum technologies.
Keywords: ROOM-TEMPERATURE; COHERENT CONTROL; SPIN; 4H; DIAMOND; PHOTON; DEFECT; QUBIT